First in-human quantitative plaque characterization with ultra-high resolution coronary photon-counting CT angiography - Mergen, Victor; Eberhard, Matthias; Manka, Robert; Euler, André; Alkadhi, Hatem (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To assess the effect of ultra-high-resolution coronary CT angiography (CCTA) with photon-counting detector (PCD) CT on quantitative coronary plaque characterization. Materials and Methods: In this IRB-approved study, 22 plaques of 20 patients (7 women; mean age 77±8 years, mean body mass index 26.1±3.6 kg/m2) undergoing ECG-gated ultra-high-resolution CCTA with PCD-CT were included. Images were reconstructed with a smooth (Bv40) and a sharp (Bv64) vascular kernel, with quantum iterative reconstruction (strength level 4), and using a slice thickness of 0.6 mm, 0.4 mm, and 0.2 mm, respectively (field-of-view 200x200 mm2, matrix size 512x512 pixels). Reconstructions with the Bv40 kernel and slice thickness of 0.6 mm served as the reference standard. After identification of a plaque in coronary arteries with a vessel diameter ≥2 mm, plaque composition was determined using a dedicated, semi-automated plaque quantification software. Total plaque, calcified, fibrotic, and lipid-rich plaque components were quantified in all datasets. Results: Median plaque volume was highest (23.5 mm3, interquartiles 17.9 – 34.3 mm3) for reconstructions with the reference standard and lowest for ultra-high-resolution reconstructions with a slice thickness of 0.2 mm and the Bv64 kernel (18.1 mm3, interquartiles 14.1 – 25.8 mm3, p<.001). Reconstructions with the reference standard showed largest calcified (85.1%, interquartiles 76.4 – 91.1%) and smallest lipid-rich plaque components (0.5%, interquartiles 0.0 – 1.5%). Smallest calcified plaque components (75.2%, interquartiles 79.9 – 80.8%) and largest lipid-rich components (6.7%, interquartiles 5.1 – 8.4%) were found for ultra-high-resolution reconstructions with a slice thickness of 0.2 mm and the Bv64 kernel. At an identical slice thickness, volume of calcified components was always lower, and volume of lipid-rich components was always higher for reconstructions with the Bv64 kernel compared with reconstructions with the Bv40 kernel (all, p<.001). Conclusion: This patient study indicates significant differences of ultra-high-resolution scanning with photon-counting detector CT on quantitative coronary plaque characterization. Reduced blooming artifacts may allow improved visualization of fibrotic and lipid-rich plaque components with the ultra-high-resolution mode of photon-counting detector CT.